Waste Processing With Plant Media is a Path to Sustainable Tourism in Nusa Lembongan Tourism Area - I Ketut Suja (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2018)
his research was conducted in Nusa Lembongan Island, Bali, with the aim to know the waste management model which using model of pond with plant media, in accordance with Government Regulation No. 82 Year 2001 on the management of water quality and air pollution control. In maintaining the environment (green tourism) since 2000, Bali has developed Tri Hita Karana Award and Accreditation Program (THK Awards Program) to hotels in Bali. Water recycling process is one of the conditions that must be possessed by hotel industry with environmental vision. The tourism industry in Bali has a positive impact on economic growth but is suspected as a polluter of the environment. Tourism industry activities cannot be separated from the need to water. Disposable waste discharges cannot cause contamination of the environment itself. Result of physical, chemical and biological quality parameter analysis either in situ (in location) or laboratory. Quantitatively, the manmade pond has potential to become an alternative water resource and needs some process. One method of pond treatment in Indonesia are constructed wetlands due to the diversity of vegetation, the simple construction, flexible, easy and inexpensive operation and maintenance and has aesthetic value. The pollutant reducing vegetation in the pond at this research is jasmine because it is easy to grow, doesn’t need special maintenance, and from some studies it was proofed to be effective in reducing BOD and COD at average of 73%.